NITROGEN DOPED GRAPHENE FROM PALM OIL WASTE - Ria Kusuma, Kanti
ABSTRACT NITROGEN DOPED GRAPHENE FROM PALM OIL WASTE By Kanti Ria Kusuma NIM : 23015023 (Chemical Engineering Master Program) The production of palm oil in Indonesia, as well as its waste, are increasing by year. Waste from palm oil production can be used as raw material for high value added products. One of the product that can be made from oil palm biomass is graphene. Graphene is a planar sheet of sp2 bonded carbon atoms densely packed in a honeycomb crystal lattice. Graphene commonly used in electronic device such as field effect transistor and energy storage such as supercapacitor. Due to its high porosity and good conductivity, graphene is suitable as supercapacitor electrode material. Recently, there are many sophiscated methods to produce graphene. The methods are micromechanical exfoliation using scocth tape, reduction of graphene oxide, and chemical vapor deposition. The alternative method to produce graphene is simple pyrolysis. Pyrolysis is a thermochemical decomposition of organic material in the absence of oxygen. This research is focused on manufacturing of graphene from palm oil waste by pyrolisis. This research investigated the effect of concentration of FeCl3 catalyst and process temperature. Graphene from empty fruit bunch have a surface area of 63.12-823.46 m2/g and pore size of 1.3 – 15.0 nm. While graphene made from oil palm shell have surface area 81.75-1152.78 m2/g and pore size 1.3 – 3.1 nm. In this study graphene is used as a working electrode on an asymmetric hybrid supercapacitor with nickel oxide as a counter electrode. This empty fruit bunch-based supercapacitor cell is capable of producing a capacitance of 120.92 F/g, while oil palm shell-based supercapacitor has a capacitance of 81.92 F/g. Keywords: biomass, graphene, pyrolysis, supercapacitor